2012
DOI: 10.1128/jvi.00981-12
|View full text |Cite
|
Sign up to set email alerts
|

Memory CD8+T Cells Specific for a Single Immunodominant or Subdominant Determinant Induced by Peptide-Dendritic Cell Immunization Protect from an Acute Lethal Viral Disease

Abstract: The antigens recognized by individual CD8+T cells are small peptides bound to major histocompatibility complex (MHC) class I molecules. The CD8+T cell response to a virus is restricted to several peptides, and the magnitudes of the effector as well as memory phases of the response to the individual peptides are generally hierarchical. The peptide eliciting a stronger response is called immunodominant (ID), and those with smaller-magnitude responses are termed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 56 publications
2
28
0
Order By: Relevance
“…This suggests that the generation, maintenance, and recall response of CD8 M to nonattenuated VACV may be less dependent on T H than strains with poorer replicative potential. Another reason for the differences might be that, similar to SalekArdakani et al (25), we determined polyclonal responses against a natural epitope shared by VACV and ECTV (31,36) rather than TCR transgenic responses to ectopic determinants (14, 21-23, 37, 38). In addition to attenuation, other factors that may affect the need for T H and protective capacity are the dose of VACV and the route of inoculation (20,25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that the generation, maintenance, and recall response of CD8 M to nonattenuated VACV may be less dependent on T H than strains with poorer replicative potential. Another reason for the differences might be that, similar to SalekArdakani et al (25), we determined polyclonal responses against a natural epitope shared by VACV and ECTV (31,36) rather than TCR transgenic responses to ectopic determinants (14, 21-23, 37, 38). In addition to attenuation, other factors that may affect the need for T H and protective capacity are the dose of VACV and the route of inoculation (20,25).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that CD8 M induced by VACV immunization become CD8 E and protect mice from mousepox, strongly suggesting that the establishment of a pool of CD8 M cells is one of the mechanisms whereby the smallpox vaccine protects from pathogenic OPVs (10,11,36). Given the importance of CD8 M induced by VACV in protection from lethal OPVs, we thought that it was important to determine the impact of T H in the establishment of this form of protective immunity.…”
Section: Discussionmentioning
confidence: 99%
“…We limited the analysis to peptides that contain 9-11 residues, because the large majority conforms to this length while a small fraction contains longer peptides. the protective potential of individual antigenic determinants, which were mostly focused on a few rapidly detectable specificities (31)(32)(33)(34). Therefore, the actual array of critical antigenic determinants driving protective TCD8 responses during a natural infection or after vaccination remains unknown.…”
Section: Resultsmentioning
confidence: 99%
“…CD8 + T cells specific to epitopes encoded by pathogens are generally organized into hierarchies based on the magnitude of the response (immunodominance). The most immunodominant epitopes are not necessarily the most protective [20][21][22][23], and perturbations of the epitope hierarchy may lead to different immune response outcomes [22]. The relationship between CD8 + T cell hierarchy and cross-reactivity could be significant in DENV pathogenesis and protection.…”
mentioning
confidence: 99%
“…CD8 + T cells specific to epitopes encoded by pathogens are generally organized into hierarchies based on the magnitude of the response (immunodominance). The most immunodominant epitopes are not necessarily the most protective [20][21][22][23], and perturbations of the epitope bs_bs_banner Clinical and Experimental Immunology ORIGINAL ARTICLE …”
mentioning
confidence: 99%